Association Of Electroencephalogram Patterns With Ammonia Levels In Hepatic Encephalopathy Patients - Fatima, Anam; Shah, Faridullah; Khan, Hareema Saeed; Rauf, Kashif; Jalil, Asif; Akhter, Muhammad Saleem (Journal of Rawalpindi Medical College, 2023)
Objective: To find out the association between electroencephalogram (EEG) and hepatic encephalopathy. Methodology: This cross-sectional study included 100 patients (with the age of52.5±6.09years for males and 51.7 ± 6.10 years for females) of reported hepatic encephalopathy, visiting the medical department (indoor and OPD) at Federal Government Polyclinic Hospital, Islamabad. The study was conducted from January 2020 to May 2021. Patients who had known epileptic and structural brain lesions or strokes were excluded from the study. Statistical analysis was done using GraphPad Prism software. The significance of data (p-value or R2 value) was calculated through a two-tailed test or correlation coefficient. Results: All the patients in hepatic encephalopathy grade IV reported abnormal EEG representing triphasic waves and flattening of EEG pattern. There was no correlation observed between age, gender and hepatic encephalopathy grades. However, a significant correlation (R2= 0.9032) was observed between serum ammonia levels and hepatic encephalopathy grades. Elevated serum ammonia levels depicted the severity of hepatic encephalopathy. Overall, the percentage of patients with abnormal EEG increased with increasing grade of hepatic encephalopathy. It was quite intriguing to note that EEG, being the common method to diagnose hepatic encephalopathy grades, is not dependent on patients’ socio-economic status. Conclusion: Data concluded that serum ammonia levels are well associated with the progression of hepatic encephalopathy. Moreover, the EEG patter provides the appropriate information about the neurological abnormalities associated with the severity of hepatic encephalopathy. Hence, serum ammonia levels and EEG both should accurately be used as indicators for diagnosis and monitoring the response to the treatment of various grades of hepatic encephalopathy. Data warrant further investigations to get a better insight into hepatic encephalopathy's relationship with EEG patterns through the inclusion of molecular parameters.